Left Atrial Appendage Occlusion in High Bleeding Risk Patients - Pierluigi Merella; Giovanni Lorenzoni; Alessandro P. Delitala; Filomena Sechi; Federica Decandia; Graziana Viola; Paola Berne; Gianluca Deiana; Patrizio Mazzone; Gavino Casu (Journal of Interventional Cardiology)
Objectives. The aim of this study was to investigate the outcomes of left atrial appendage occlusion (LAAO) in high bleeding risk patients suffering atrial fibrillation (AF) and to analyze the different antithrombotic therapies following the intervention. Background. Methods. This monocentric study included 68 patients with nonvalvular AF with an absolute contraindication to OAT or at high bleeding risk. Follow-up was done with a clinical visit at 3-6-12 months. Results. Successful LAAO was achieved in 67/68 patients. At discharge, 32/68 patients were on dual antiplatelet therapy (APT), 34/68 were without any antithrombotic therapy or with a single antiplatelet drug, and 2/68 were on anticoagulant therapy. At three-month follow-up visit, 73.6% of the patients did not receive dual APT, of whom 14.7% had no thrombotic therapy and 58.9% were on single antiplatelet therapy. During a follow-up of 1.4 ± 0.9 years, 3/62 patients had late adverse effects (2 device-related thrombus without clinical consequences and 1 extracranial bleeding). The device-related thrombosis was not related to the antithrombotic therapy. Conclusions. LAAO is feasible and safe and prevents stroke in patients with AF with contraindication to oral anticoagulant therapy. After LAAO, single antiplatelet therapy seems to be a safe alternative to dual antiplatelet therapy, especially in patients at high bleeding risk. No benefit has been observed with dual APT.